Reinforcing effect of polypropylene waste strips on compacted lateritic soils - Marçal, Régis [UNESP]; Lodi, Paulo César [UNESP]; Correia, Natália de Souza; Giacheti, Heraldo Luiz [UNESP]; Rodrigues, Roger Augusto [UNESP]; McCartney, John S. (MDPI, 2020)
This study evaluated the strength properties of compacted lateritic soils reinforced with polypropylene (PP) waste strips cut from recycled plastic packing with the goal of promoting sustainability through using local materials for engineering work and reusing waste materials as low-cost reinforcements. Waste PP strips with widths of 15 mm and different lengths were uniformly mixed with clayey sand (SC) and clay (CL) soils with the goal of using these materials as low-cost fiber reinforcements. The impact of different PP strip contents (0.25% to 2.0%) and lengths (10, 15, 20, and 30 mm) on the unconfined compressive strength (UCS) of the soils revealed an optimum combination of PP strip content and length. Statistical analysis showed that PP strip content has a greater effect than the PP strip length on the UCS for both soils. Results led to the definition of an empirical equation to estimate the UCS of strip-reinforced soils. The results from direct shear tests indicate that the SC soil showed an increase in both apparent cohesion and friction angle after reinforcement, while the CL soil only showed an increase in friction angle after reinforcement. California bearing ratio (CBR) tests indicate that the SC soil experienced a 70% increase in CBR after reinforcement, while the CBR of the CL soil was not affected by strip inclusion.
Keywords: Geotechnical properties; Polypropylene strips; Soil improvement; Sustainable reuse of plastic waste